2019
DOI: 10.1103/physreve.100.012138
|View full text |Cite
|
Sign up to set email alerts
|

Three-level laser heat engine at optimal performance with ecological function

Abstract: Although classical and quantum heat engines work on entirely different fundamental principles, there is an underlying similarity. For instance, the form of efficiency at optimal performance may be similar for both types of engines. In this work, we study a three-level laser quantum heat engine operating at maximum ecological function (EF) which represents a compromise between the power output and the loss of power due to entropy production. We derive analytic expressions for efficiency under the assumptions of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 77 publications
2
14
0
Order By: Relevance
“…which concurs with the efficiency of the endoreversible and symmetric low-dissipation models of heat engines [29,47]. The results are not surprising as in the hightemperature regime (classical regime), the engines are expected to behave like classical heat engines [24,28,48]. Eq.…”
supporting
confidence: 78%
See 3 more Smart Citations
“…which concurs with the efficiency of the endoreversible and symmetric low-dissipation models of heat engines [29,47]. The results are not surprising as in the hightemperature regime (classical regime), the engines are expected to behave like classical heat engines [24,28,48]. Eq.…”
supporting
confidence: 78%
“…The universality of the EMOF was first formally proven by Zhang and coauthors [53] by using the framework of stochastic thermodynamics. The first two terms 3η C /4 and η 2 C /32 were also obtained for endoreversible [29,54], low-dissipation [47], minimally nonlinear irreversible [55] and some other models of classical and quantum heat engines [28,54,56].…”
Section: Low-temperature Regimementioning
confidence: 80%
See 2 more Smart Citations
“…56,59 Further, it has been shown that the quadratic coefficient 1/32 is also universal for the strongly coupling systems with the left right symmetry. 56 The universality of such an efficiency has been investigated in different heat engines such as stochastic Brownian heat engines, 60 Feynman ratchet heat engines, 60 quantum dot heat engines, 60 low-dissipation heat engines, 61 classical heat engines, 62 and minimally nonlinear irreversible heat engines 63 and laser quantum heat engine 64 Another optimization criterion is Efficient power, defined as the product of efficiency and power (ηP), pays equal attention to both the efficiency and the poweroutput, was first proposed in Refs. [65,66] and further extended in studies.…”
Section: Introductionmentioning
confidence: 99%